2022
DOI: 10.3390/cells11203246
|View full text |Cite
|
Sign up to set email alerts
|

NGF Prevents Loss of TrkA/VEGFR2 Cells, and VEGF Isoform Dysregulation in the Retina of Adult Diabetic Rats

Abstract: Among the factors involved in diabetic retinopathy (DR), nerve growth factor (NGF) and vascular endothelial growth factor A (VEGFA) have been shown to affect both neuronal survival and vascular function, suggesting that their crosstalk might influence DR outcomes. To address this question, the administration of eye drops containing NGF (ed-NGF) to adult Sprague Dawley rats receiving streptozotocin (STZ) intraperitoneal injection was used as an experimental paradigm to investigate NGF modulation of VEGFA and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In contrast to Scg3, VEGF drives DR-associated vascular pathology primarily through increased levels of ligand with estimates of a >100-fold increase in VEGF-A in the vitreous of PDR patients [ 40 , 41 ]. The low specificity and absence of apparent DR-related differential binding of VEGF observed in our study is consistent with other reports that VEGF receptors (VEGFRs) are minimally elevated or even decreased in diabetic rodents and patients [ 41 , 42 ]. The binding pattern is also consistent with the ubiquitous presence of VEGFRs in retinal vessels in control and DR mice, as discussed previously [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to Scg3, VEGF drives DR-associated vascular pathology primarily through increased levels of ligand with estimates of a >100-fold increase in VEGF-A in the vitreous of PDR patients [ 40 , 41 ]. The low specificity and absence of apparent DR-related differential binding of VEGF observed in our study is consistent with other reports that VEGF receptors (VEGFRs) are minimally elevated or even decreased in diabetic rodents and patients [ 41 , 42 ]. The binding pattern is also consistent with the ubiquitous presence of VEGFRs in retinal vessels in control and DR mice, as discussed previously [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…More clinical data support the relationship between repeated anti-VEGF injections and the development of ocular hypertension or glaucoma [ 61 , 62 ]. Moreover, very recent preclinical data suggest that the effects of VEGF in DR can be modulated by the concomitant presence of NGF [ 63 ]. Therefore, regulating factors upstream of VEGF have received attention as a desirable therapeutic approach to eliminating off-target effects.…”
Section: Management Of Neovascular Retinal Diseasesmentioning
confidence: 99%
“…Thus, cannabinoid drugs may have both neuroprotective and vasoprotective effects in DR. VEGFA is known to exert a neuroprotective effect via the VEGF receptor 2. The topical administration of nerve growth factor (NGF) reduces inflammatory and pro-apoptotic intracellular signals and maintains VEGF receptor 2 expression in the RGCs of diabetic rats [ 115 ]. In the retinas of diabetic rats, the expression of VEGF receptor 2 is decreased.…”
Section: Therapeutic Approaches For Retinal Cell Death In Drmentioning
confidence: 99%
“…In the retinas of diabetic rats, the expression of VEGF receptor 2 is decreased. Thus, NGF may contribute to the switch from proangiogenic and apoptotic phases to the neuroprotective phase of VEGF in early DR [ 115 ]. Another study indicated that the topical administration of NGF successfully prevented RGC loss, pericyte loss, and acellular capillary development in animal diabetic models [ 116 ].…”
Section: Therapeutic Approaches For Retinal Cell Death In Drmentioning
confidence: 99%